1990
DOI: 10.2166/wst.1990.0139
|View full text |Cite
|
Sign up to set email alerts
|

Packed-Cage RBC with Combined Cultivation of Suspended and Fixed-Film Biomass

Abstract: The situation in the treatment of wastewaters from small sources in Czechoslovakia has been discussed and two types of manufactured rotating biological contactors have been described. The evaluation of RBCs' operation showed the main disadvantages of the contactors with conventional discs, viz. the low 0C and low mixing effect. In a newly designed RBC, the discs or packets of discs were replaced by a cage packed with a random medium. The cage was equipped with tubular aeration and mixing elements. The long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…For P / V L values (∼60 W m −3 ) similar to those in Zlokarnik's work,11 and using eqn (6) to calculate k L a the OTE works out to be 0.3 kg kWh −1 . In the case of the h‐RPB, the study by Wanner et al 6 gives the OTE values for a pilot‐scale and full‐scale unit as 0.9 kg kWh −1 and 0.63 kg kWh −1 respectively. A comparison between these values clearly establishes the higher efficiency of the h‐RPB for full‐scale units.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For P / V L values (∼60 W m −3 ) similar to those in Zlokarnik's work,11 and using eqn (6) to calculate k L a the OTE works out to be 0.3 kg kWh −1 . In the case of the h‐RPB, the study by Wanner et al 6 gives the OTE values for a pilot‐scale and full‐scale unit as 0.9 kg kWh −1 and 0.63 kg kWh −1 respectively. A comparison between these values clearly establishes the higher efficiency of the h‐RPB for full‐scale units.…”
Section: Resultsmentioning
confidence: 99%
“…Also, for lower influent flowrates (<1 m 3 h −1 ) the authors have reported completely mixed flow conditions. Wanner et al 6 carried out pilot plant‐ and full‐scale studies on aerobic h‐RPBs. They reported removal efficiencies of 92–97% in the case of the pilot plant (0.33 m cage diameter, 0.85 m length).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This compares well with the typical values of surface area in conventional reactors 5 such as packed columns (25-200 m 2 /m 3 of reactor), bubble columns (25-500 m 2 /m 3 of reactor), and stirred reactors (100-1000 m 2 /m 3 of reactor). Wanner et al 6 developed an RBC system consisting of a cage filled with random packings, which is shown schematically in Figure 2. The cage was constructed with wire mesh netting and was filled with cylindrical plastic elements.…”
Section: Media For Rbcsmentioning
confidence: 99%
“…The cage was constructed with wire mesh netting and was filled with cylindrical plastic elements. Wanner et al 6 reported that their entire assembly provided a contact area of 10.5 m 2 . For the dimensions given in their paper, the interfacial area is 100 m 2 /m 3 of reactor volume, which is the same as that of standard-density media (Figure 1B).…”
Section: Media For Rbcsmentioning
confidence: 99%